Proceedings of the 'Working together to consider the role of biofortification in the global food chain' workshop. Issue 4 (8th November 2018) - Lockyer, S.; White, A.; Walton, J.; Buttriss, J. L.
Abstract: A workshop, jointly hosted by the British Nutrition Foundation, HarvestPlus and the UK government's Department for International Development, was held in May 2018 in London to discuss the potential of introducing biofortified foods into the UK market. Forty delegates from academia, the food industry and non‐government organisations (NGOs) attended. The workshop included presentations outlining the findings of research into the efficacy of biofortified crops in developing countries, the current situation in the UK in terms of micronutrient intakes and status, regulatory issues and consumer acceptability insights. Group work focused on challenges and opportunities relating to introducing biofortified foods into developed markets, in particular aspects relating to consumers ( e.g . awareness and understanding of micronutrients and intakes in the UK; potential demand and marketing strategies for biofortified foods); crop growers ( e.g . would existing biofortified crops be suitable for the UK climate and who would absorb any additional related costs?); the relevance and acceptability of various biofortified foods in the UK ( e.g . based on current dietary patterns and preferences); manufacturers and retailers ( e.g . smallholders in the developing world could be linked to the UK food industry; nutrition claims could be utilised); public health ( e.g . identification of priorities; potential beneficiaries and ways to target these); regulation ( e.g . could a minimum crop micronutrient content be made mandatory?); and research ( e.g . to further prove efficacy; consumer insights). Four themes emerged: crop research; consumer education and awareness; standards; and public health research. These were used to identify various challenges, opportunities, beneficiaries, stakeholders, necessary actions and immediate next steps that could form the basis of future work streams designed to explore bringing biofortified foods to the UK market.